Free Yourself From the Role (LEARNing Landscapes, 2008)
The author shares a song he wrote to represent his views about the movement among educators to redefine for themselves their roles and practices. He also reflects on his song-writing process.The song and accompanying reflection serve to question stereotypical views of knowledge and suggest the need for educators to embrace a more artful approach to teaching and learning.
Keywords: educator; role; song; artful approach; teaching; learning